Defining ethnic, national, and dual identities: Structure, antecedents, and consequences of multiple social identities of Turkish‐origin high school students in Germany. (29th May 2017) - Martiny, Sarah E.; Froehlich, Laura; Deaux, Kay; Mok, Sog Yee
Abstract: The number of immigrants and children born to immigrant parents in Europe has risen steadily. Related to debates as to how best integrate immigrants, research points to the importance of investigating the structure as well as antecedents and consequences of immigrants' multiple identities. Here, we explore the relationship between three different identities endorsed by adolescent Turkish‐origin immigrants in Germany: ethnic identity (i.e., Turkish identity), national identity (i.e., German identity), and dual identity (i.e., German–Turkish identity). In two studies, Turkish‐origin adolescents in Germany (Study 1: N = 91, age: M = 15.18, SD = 0.97; Study 2: N = 95, age: M = 15.26, SD = 0.90) completed measures of multiple identities, contact with native Germans, and feelings of being integrated in Germany. Results show that adolescents' dual identity was positively related to their national identity but negatively related to their ethnic identity. Ethnic and national identities were also negatively related. Further, when Turkish‐origin students had more contact with native Germans, they felt more at home in Germany, mediated by their national and dual identity. Results are discussed in terms of the role that identity construction plays in the integration of immigrants into host societies.